2020
DOI: 10.33417/tsh.641049
|View full text |Cite
|
Sign up to set email alerts
|

Eski Hükümlülerin ve Denetimli Serbestlik Yükümlülerinin İstihdamı Üzerine Uygulamalı Bir Araştırma

Abstract: Bu araştırmanın temel amacı, eski hükümlülerin ve denetimli serbestlik yükümlülerinin istihdam edilmelerinde karşılaştıkları sorunları ortaya koymak ve aynı zamanda işverenlerin eski hükümlü ve denetimli serbestlik yükümlülerinin istihdamına ilişkin görüşlerini belirlemektir. Bu çalışma, kesitsel tarama deseni kullanan nicel bir araştırma olarak tasarlanmış ve bu kapsamda Türkiye'nin 81 ilinde bulunan 8234 işveren ile 1915 eski hükümlü ve denetimli serbestlik yükümlüsü çalışmaya dâhil edilmiştir. Araştırmanın … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Numerous studies have highlighted the correlation between social status acquired through labeling and an increase in criminal behavior (Krohn et al, 2014;Jolliffe et al, 2015;Savaş and Eryalçın, 2020;Gün & Önder Erol, 2023). Additionally, it has been observed that individuals who feel marginalized from society may develop an inflated sense of pride, leading to the continuation of their criminal acts.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have highlighted the correlation between social status acquired through labeling and an increase in criminal behavior (Krohn et al, 2014;Jolliffe et al, 2015;Savaş and Eryalçın, 2020;Gün & Önder Erol, 2023). Additionally, it has been observed that individuals who feel marginalized from society may develop an inflated sense of pride, leading to the continuation of their criminal acts.…”
Section: Discussionmentioning
confidence: 99%